Waltheria glabribracteata (Byttnerioideae, Malvaceae), a new species with elongate-plumose stigmas from South America - Coutinho, Thales Silva; Alves, Marccus (Phytotaxa, 2020)
A new Waltheria species (Malvaceae) is described and illustrated here. Waltheria glabribracteata is known from ecotone areas in Brazil and Bolivia and can be readily distinguished from other Waltheria species by its bracts which are glabrous on the adaxial surface. This study presents a description of the new taxon, taxonomic comments, a distribution map, conservation status and an illustration.